2024
DOI: 10.1002/smll.202309680
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐Assisted Large‐Scale Assembly and Differential Patterning of DNA Origami Lattices

Svetozar Gavrilović,
Gereon Andreas Brüggenthies,
Johann Moritz Weck
et al.

Abstract: Nanofabrication has experienced a big boost with the invention of DNA origami, enabling the production and assembly of complex nanoscale structures that may be able to unlock fully new functionalities in biology and beyond. The remarkable precision with which these structures can be designed and produced is, however, not yet matched by their assembly dynamics, which can be extremely slow, particularly when attached to biological templates, such as membranes. Here, the rapid and controlled formation of DNA orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…16 This newly discovered biochemical function, although possibly irrelevant in vivo, could thus be exploited for the positioning of membraneattached molecules and other biomimetic features in artificial systems. 17,18 In this study, we demonstrate the successful co-reconstitution of actomyosin architectures and the MinDE system inside GUVs. Upon optimization of encapsulation conditions, time-lapse imaging revealed the MinDE-driven diffusiophoretic positioning of actomyosin rings and bundle networks at mid-cell, where we observed equatorial furrow-like invaginations breaking spherical symmetry.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…16 This newly discovered biochemical function, although possibly irrelevant in vivo, could thus be exploited for the positioning of membraneattached molecules and other biomimetic features in artificial systems. 17,18 In this study, we demonstrate the successful co-reconstitution of actomyosin architectures and the MinDE system inside GUVs. Upon optimization of encapsulation conditions, time-lapse imaging revealed the MinDE-driven diffusiophoretic positioning of actomyosin rings and bundle networks at mid-cell, where we observed equatorial furrow-like invaginations breaking spherical symmetry.…”
Section: Introductionmentioning
confidence: 66%
“…10 Interestingly, recent studies have shown the robustness and versatility of a protein-based spatial positioning toolset: the MinDE system. [16][17][18] The Escherichia coli (E. coli) Min proteins are a reaction-diffusion system able to self-organize on membranes through ATP hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations